Discrimination On The Immigrants: Migration Venezuelan To The Colombia - Yordan Gunawan; Arqam Muhammad Amrullah; Muhammad Fauzi (Faculty of Law, Merdeka University Surabaya, Indonesia, 2023)
Venezuela is facing a severe economic, political, and social crisis, with acute shortages of food, medicine, and other basic goods. At the same time, large numbers of Venezuelans left the country to migrate, causing Latin America to be hit by a massive migration crisis that never happened before. On the other hand, the Venezuelan population who migrated, especially to Colombia, experienced discrimination. Covid 19 is also making the Venezuelan conditions worsen, along with shortages of food, medicine, and health, as well as access to social services. This research aims to analyze various aspects of the Venezuelan immigrant crisis in recent years. Emphasis is placed on the importance of regional migration issues and the participation of the international community. The research used normative juridical legal research methods. The main points of this research are: a) The main social, economic, and political factors related to the humanitarian crisis, especially discrimination and migration issues in Venezuela; b) Venezuelan Migration and Refugee Issues; c) Response and participation of the international community, with particular emphasis on the activities of the European Union, the United Nations, and Latin America, in particular, Colombia. The results of this research are the discrimination that refugees from Venezuela receive due to the lack of funds they must migrate due to a corrupt government which results in them looking for easy and inexpensive alternatives to flee to other countries.